2018
DOI: 10.1186/s13068-018-1018-y
|View full text |Cite
|
Sign up to set email alerts
|

Association of improved oxidative stress tolerance and alleviation of glucose repression with superior xylose-utilization capability by a natural isolate of Saccharomyces cerevisiae

Abstract: BackgroundSaccharomyces cerevisiae wild strains generally have poor xylose-utilization capability, which is a major barrier for efficient bioconversion of lignocellulosic biomass. Laboratory adaption is commonly used to enhance xylose utilization of recombinant S. cerevisiae. Apparently, yeast cells could remodel the metabolic network for xylose metabolism. However, it still remains unclear why natural isolates of S. cerevisiae poorly utilize xylose. Here, we analyzed a unique S. cerevisiae natural isolate YB-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 83 publications
3
27
0
Order By: Relevance
“…Clustering of the expression patterns and GO term analysis of each cluster revealed that genes involved in translation, ribosome biogenesis, vesicle‐mediated transport, and cellular localization (among other related processes) were up‐regulated during growth on xylose by the strains having the XDH1 dehydrogenase, confirming that the yeast cells were indeed growing. Other genes up‐regulated during growth on xylose were enriched for pentose metabolic process, and response to oxidative stress, as also shown latter on by Cheng and co‐workers (). Some set of genes induced by xylose consumption or growth on xylose have been also observed to be up‐regulated during xylulose fermentation (see above, Mittelman & Barkai, ; Tamari et al, ).…”
Section: Transcriptome Analysis Of Nonrecombinant Xylose‐utilizing Ssupporting
confidence: 72%
See 4 more Smart Citations
“…Clustering of the expression patterns and GO term analysis of each cluster revealed that genes involved in translation, ribosome biogenesis, vesicle‐mediated transport, and cellular localization (among other related processes) were up‐regulated during growth on xylose by the strains having the XDH1 dehydrogenase, confirming that the yeast cells were indeed growing. Other genes up‐regulated during growth on xylose were enriched for pentose metabolic process, and response to oxidative stress, as also shown latter on by Cheng and co‐workers (). Some set of genes induced by xylose consumption or growth on xylose have been also observed to be up‐regulated during xylulose fermentation (see above, Mittelman & Barkai, ; Tamari et al, ).…”
Section: Transcriptome Analysis Of Nonrecombinant Xylose‐utilizing Ssupporting
confidence: 72%
“…Under these conditions strain YB2625 produced 10.9 g/L xylitol, and strain S288C produced 3.1 g/L, without significant differences in the ethanol concentration in the fermentation media. However, significant differences in the production of glycerol and acetic acid were observed (higher with S288C), as well as a slightly higher biomass produced by strain YB2625 throughout the culture (Cheng et al, ).…”
Section: Growth and Xylose Consumption By S Cerevisiaementioning
confidence: 99%
See 3 more Smart Citations